2016
DOI: 10.5588/pha.16.0001
|View full text |Cite
|
Sign up to set email alerts
|

Mixed impact of Xpert® MTB/RIF on tuberculosis diagnosis in Cambodia

Abstract: Although utilization of Xpert was low, it may have contributed to an increase in evaluations for possible MDR-TB and a decline in empiric treatment for PLHIV when available as POC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“… 22 - 25 In a study conducted in Rwanda, in which both methods were applied in the same group of patients, Ngbonziza et al found a 32.3% gain in diagnostic power, 22 whereas Cowan et al reported a 69.0% diagnostic gain in a study conducted in Mozambique. 23 In a population of 401 HIV-infected individuals in Cambodia, Auld et al 24 reported a diagnostic gain of only 26.0% attributed to the use of the Xpert MTB/RIF test. Evaluating routine program data in 18 countries, Ardizzoni et al 25 observed that the use of the Xpert MTB/RIF test resulted in a mean relative diagnostic gain of 42.3% over the use of sputum smear microscopy.…”
Section: Discussionmentioning
confidence: 99%
“… 22 - 25 In a study conducted in Rwanda, in which both methods were applied in the same group of patients, Ngbonziza et al found a 32.3% gain in diagnostic power, 22 whereas Cowan et al reported a 69.0% diagnostic gain in a study conducted in Mozambique. 23 In a population of 401 HIV-infected individuals in Cambodia, Auld et al 24 reported a diagnostic gain of only 26.0% attributed to the use of the Xpert MTB/RIF test. Evaluating routine program data in 18 countries, Ardizzoni et al 25 observed that the use of the Xpert MTB/RIF test resulted in a mean relative diagnostic gain of 42.3% over the use of sputum smear microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…A revised guidelines were published in 2013 endorsing the use for diagnostic pulmonary TB, pediatric TB, extrapulmonary TB, rifampicin resistance, and for TB/HIV coinfection cases. In Brazil, this rapid molecular test (TRM) was introduced, in 2014 [ 6 , 7 ]. However, conventional methods of smears and cultures continue to be considered the gold standard for diagnosis and monitoring the treatment for TB, despite their limitations such as low sensitivity and long incubation period [ 8 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Brum et al reported that the Xpert test is sensitive and specific in cases of pulmonary TB among populations living with HIV, thereby showing diagnostic and treatment benefits, especially in cases with negative smear results [52,53]. Auld et al concluded that the molecular test contributed to an increase in TB-MDR detection and observed a decline in the empirical treatment of this population, contributing to timely diagnosis and treatment [7].…”
Section: Plos Onementioning
confidence: 99%
“…A revised guidelines were published in 2013 endorsing the use for diagnostic pulmonary TB, pediatric TB, extrapulmonary TB, rifampicin resistance, and for TB/HIV coinfection cases. In Brazil, this rapid molecular test (TRM) was introduced, in 2014 [6,7]. However, conventional methods of smears and cultures continue to be considered the gold standard for diagnosis and monitoring the treatment for TB, despite their limitations such as low sensitivity and long incubation period [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%